Odpowiedzi

  • Roma
  • Community Manager
2010-01-06T13:06:57+01:00
A.(a+b)²-(a-b)² = a²+2ab+b²-a²+2ab-b² = 4ab ≠ 2ab

b.(a+b)³-(a-b)³= a³ + 3a²b + 3ab² + b³ - a³ + 3a²b - 3ab² + b³ = 6a²b + 2b³ = 2b(3a² + b) ≠ 2b(b²+3a)

c.(a+b)(a²-ab+b²)-(a-b)(a²+ab+b²) = a³ - a²b + ab² + a²b - ab²+ b³ - a³ - a²b - ab² + a²b + ab² + b³ = 2b³

Prawdziwa jest równość c.
3 3 3
2010-01-06T13:07:55+01:00
A)(a+b)²-(a-b)²=2ab
L=(a+b)²-(a-b)²= a²+2ab+b²-(a²-2ab+b²)=a²+2ab+b²-a²+2ab-b²=4ab≠P
Ta równość nie jest prawdziwa.
b)(a+b)³-(a-b)³=2b(b²=3a)
L=(a+b)³-(a-b)³=a³+3 a²b+3ab²+b³-(a³-3 a²b+3ab²-b³)= =a³+3 a²b+3ab²+b³-a³+3 a²b-3ab²+b³=2b³+6a²b=2b(b²+3a²)≠P
Ta równość nie jest prawdziwa.
c)(a+b)(a²-ab+b²)-(a-b)(a²+ab+b²)=2b³
L=a³+b³-(a³-b³)=a³+b³-a³+b³=2b³=P
Ta równość jest prawdziwa.
1 4 1
2010-01-06T13:15:44+01:00
(a+b)²-(a-b)²=2ab
a²+2ab+b²-(a²-2ab+b²)=2ab
a²+2ab+b²-a²+2ab-b²=2ab
4ab=2ab
ab=½ab

(a+b)³-(a-b)³=2b(b²+3a)
a³+3ab+b³-(a³-3ab+b³)=2b³+6ab
a+3ab+b³-a³+3ab-b³=2b³+6ab
6ab=2b³+6ab
ab=2b²/6+1


(a+b)(a²-ab+b²)-(a-b)(a²+ab+b²)=2b³
a³-a²b+ab²+a²b-ab²+b³-(a³+a²b-b³-a²b-ab²-b³=2b³
a³-a²b+ab²+a²b-ab²+b³-a³+a²b-b³-a²b+b³=2b³
b³=2b³
b=ab°
b=1